Computer Graphics : Using OpenGL - Hill, Francis S.; Kelley, Stephen M., 1980- (Pearson Prentice Hall, 2007)
Updated throughout for the latest developments and technologies, this text combines the principles and major techniques in computer graphics with state-of-the-art examples that relate to things students see everyday on the Internet and in computer-generated movies. Practical, accessible, and integrated in approach, it carefully presents each concept, explains the underlying mathematics, shows how to translate the math into program code, and displays the result